Potential Valproate Acid Interaction with Enteral Feedings - A Case Report - Suzana Mustafa; Siti Latifah Azirah Mohd Noor; Siti Hamisah Said; Nazmi Liana Azmi (Asian Journal of Medicine & Health Sciences, 2021)
For most antiepilepsy drugs including valproic acid (VPA), co-administration with food can slow down the absorption rate, but this does not have a clinically relevant effect on the extent of absorption and area under the curve. However, limited data are available on enteral nutrition interaction with VPA. Nonetheless, it is possible for a medication to have a lack data on drug-food interactions but have significant absorption changes when co-administered with enteral nutrition. We describe a case of a 32-year-old man with myoclonic jerking movement at both upper limbs and lower limbs with underlying diffuse cortical dysfunction. The patient receiving enteral VPA syrup dose experienced a clinically significant decrease in serum concentration when high protein enteral feeding was initiated. There was no significant change in VPA serum concentration although the doses were separated from the feeding by two to three hours. By escalating the dosing frequency of VPA from BD to TDS, it significantly increased VPA serum concentration. The interaction between nutrients and highly protein-bound drugs is a problem of great relevance in clinical practice due to potential changes in the expected effects of the drug. The clinical practice of separating phenytoin from enteral feeding was applied in this case however, it was unsuccessful. Therefore, when using enteral feeding concomitantly with enteral VPA, clinicians may consider increasing VPA frequency to TDS dosing.